Penerapan Metode Simulasi Sebagai Upaya Meningkatkan Pemahaman Konsep Komponen Penyusun Bangun Ruang di Kelas VI SDN Bendogerit 2 Kota Blitar - Ericca Retna Kusumawati (Civiliza Publishing, 2021)
Abstract. Mathematics is a science that is obtained from the process of thinking, so to build mathematical concepts can not be instant or fast. There needs to be a process of planting concepts that is carried out gradually in learning mathematics. In the classroom building lesson in Class VI SDN Bendogerit 2, Sananwetan District, Blitar City, for the 2020/2021 academic year, it can be seen that there are still many students who do not understand the concept. This is because students in this learning year do online learning, so the teacher does not teach children directly. On the other hand, in online learning, the results obtained by students have not yet reached completeness, so research on mathematics learning is needed. The research used is a qualitative research on learning Mathematics with the type of Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The method used to solve problems in learning the Spatial Building Component is the Simulation method, which is a training method that demonstrates something in the form of an imitation (eating) that is similar to the real situation.